Promises and agreements philosophical essays - Sheinman, Hanoch (New York ; Oxford : Oxford University Press, 2011)
Comprising 16 original contributions, this is the first collection of philosophical papers on promises and agreements topics which are enjoying a renaissance in social, moral and legal philosophy.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Includes bibliographical references and index.
Keywords: Promises; Contracts; Duty